2019
DOI: 10.3390/cancers11081065
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of SHIP2 by Hepatitis B Virus X Promotes the Metastasis and Chemoresistance of Hepatocellular Carcinoma through SKP2

Abstract: Hepatitis B virus (HBV)-encoded X protein (HBx) plays an important role in the development of hepatocellular carcinoma (HCC). The protein SH2 domain containing inositol 5-phosphatase 2 (SHIP2) belongs to the family of enzymes that dephosphorylate the 5 position of PI(3,4,5)P3 to produce PI(3,4)P2. Expression of SHIP2 has been associated with several cancers including HCC. However, its role in the development of HBV-related HCC remains elusive. In this study, we performed tissue microarray analysis using 49 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Red guavas were kindly provided by a farmer, Lin Chao Hsiung (A Fong guava farm, Houbi Dist., Tainan City 731, Taiwan). Doxorubicin, Erlotinib (Tarceva; Roche, Basel, Germany) and Gefitinib (Iressa; Astra Zeneca, London, England) were dissolved in dimethyl sulfoxide (DMSO) and the concentrations of drugs were referred to previous studies [15,25,30]…”
Section: Methodsmentioning
confidence: 99%
“…Red guavas were kindly provided by a farmer, Lin Chao Hsiung (A Fong guava farm, Houbi Dist., Tainan City 731, Taiwan). Doxorubicin, Erlotinib (Tarceva; Roche, Basel, Germany) and Gefitinib (Iressa; Astra Zeneca, London, England) were dissolved in dimethyl sulfoxide (DMSO) and the concentrations of drugs were referred to previous studies [15,25,30]…”
Section: Methodsmentioning
confidence: 99%
“…Our research group and other groups have published several articles on HBx protein promoted chemotherapeutic resistance in HCC[ 65 - 67 ]. A recently published paper concludes that HBx protein leads to resistance to the chemotherapy drug 5-Fluorouracil in HCC by downregulating SHIP2 through SKP2[ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research group and other groups have published several articles on HBx protein promoted chemotherapeutic resistance in HCC[ 65 - 67 ]. A recently published paper concludes that HBx protein leads to resistance to the chemotherapy drug 5-Fluorouracil in HCC by downregulating SHIP2 through SKP2[ 65 ]. We also reported that HBx protein can promote Dox chemoresistance in HCC through overexpression of Variant 1 of KIAA0101[ 66 ] and Transcript variant 2 of the chemokine-like factor (CKLF1)[ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is shown in vitro experiments that HBx induces Skp2 expression and thereby down-regulates SHIP2 by inducing a notable accumulation of polyubiquitinated SHIP2 in HCC cells. The down-regulation of SHIP2 leads to HCC cell migration, elevated glucose uptake and drug resistance to 5-Fluorouracil (5-FU) ( 89 ).…”
Section: Hbxmentioning
confidence: 99%